2015
DOI: 10.5430/ijh.v2n1p5
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting nursing cultural competency in private hospitals at Bangkok, Thailand

Abstract: Background: Cultural competency is particularly important in healthcare industry nowadays, where cultural beliefs have a significant impact on care access, treatment choices, effectiveness of nursing care, and other aspects of patient care. This study aimed to explore the level of cultural competency and the factors affecting the cultural competency of nurses, from two medium-size private hospitals in Bangkok, Thailand with similarity in therapeutic specialties and other characteristics in three categories: mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 9 publications
(11 reference statements)
4
9
0
Order By: Relevance
“…The lowest scores were found among nurses aged 35–39. This finding is almost similar to the findings reported by Bunjitpomol and her colleagues in that knowledge of cultural competence is positively associated with age and responsibility [ 17 ]. In the same line, another study investigated cultural competence among nurses in Israel, found a positive relationship between cultural skills and age/years of experience [ 18 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The lowest scores were found among nurses aged 35–39. This finding is almost similar to the findings reported by Bunjitpomol and her colleagues in that knowledge of cultural competence is positively associated with age and responsibility [ 17 ]. In the same line, another study investigated cultural competence among nurses in Israel, found a positive relationship between cultural skills and age/years of experience [ 18 ].…”
Section: Discussionsupporting
confidence: 91%
“…Language barriers between care providers and patients have often been reported as obstacles to the provision of culturally competent care [ 5 , 17 ]. However, critical cultural competence (CCC) can also be affected by the ethnicity of both the healthcare providers and patients.…”
Section: Discussionmentioning
confidence: 99%
“…It has been highlighted that a younger generation such as nursing students and young nurses are considered more receptive towards culturally diverse populations (Almutairi et al 2017;Bunjitpimol et al 2016). Through their frequent travelling and foreign languages education, they quickly adapt to new and foreign situations, and are perhaps more exposed to cultural education compared to nurses educated in past decades.…”
Section: Nurses Cultural Competence and Sociodemographic Characteristicsmentioning
confidence: 99%
“…Studies amongst nurses and physicians from Switzerland revealed that lack of practical experience of caring for diverse population and lack of or inadequate cross-cultural training was associated with poor cultural awareness (Casillas et al 2014). Therefore, it is recommended that regular education and cultural competence training for both qualified nurses and student nurses should be provided (Bunjitpimol et al 2016;Gallagher and Polanin 2015). One of the methods in cultural training is exposure to a culturally diverse environment, e.g.…”
Section: Nurses Cultural Competence and Sociodemographic Characteristicsmentioning
confidence: 99%
“…However, Thailand should focus more towards cultural training culturally sensitive and care for the healthcare workers in international hospitals by promoting the knowledge, attitude and practices among their medical staff. 3 - 6 Nurse should be trained to communicate in international language in fluent way so that patients can understand them easily and respond. 7 Studies have proved that healthcare workers exposure regarding cultural competence is very imperative in motivating the patients in organization.…”
Section: Introductionmentioning
confidence: 99%